2022
DOI: 10.3390/biology11121837
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Study of Mangostin Compounds and Its Derivatives as Inhibitors of α-Glucosidase Enzymes for Anti-Diabetic Studies

Abstract: Diabetes is a chronic disease with a high mortality rate worldwide and can cause other diseases such as kidney damage, narrowing of blood vessels, and heart disease. The concomitant use of drugs such as metformin, sulfonylurea, miglitol, and acarbose may cause side effects with long-term administration. Therefore, natural ingredients are the best choice, considering that their long-term side effects are not significant. One of the compounds that can be used as a candidate antidiabetic is mangostin; however, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…For example, Faisal Usman et al [ 54 ], Qirou Wang et al [ 55 ], and Juan Cardozo-Muñoz et al [ 56 ] conducted computational experiments without a positive control, resulting in insufficient evidence to support the reliability of their docking results for α-mangostin and α -glucosidase. On the other hand, Nina Artanti et al [ 57 ] and Ahmad Fariz Maulana et al [ 58 ] used acarbose as a positive control, but their docking results did not accurately reflect the in vitro experimental results. In this study, α-mangostin was demonstrated to be a potent α -glucosidase inhibitor, with an IC 50 value of 1.90 ± 0.10 μg/mL (equivalent to 4.63 ± 0.24 μM), whereas the IC 50 value of acarbose was 134.56 ± 3.02 μg/mL (equivalent to 204.93 ± 4.60 μM).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Faisal Usman et al [ 54 ], Qirou Wang et al [ 55 ], and Juan Cardozo-Muñoz et al [ 56 ] conducted computational experiments without a positive control, resulting in insufficient evidence to support the reliability of their docking results for α-mangostin and α -glucosidase. On the other hand, Nina Artanti et al [ 57 ] and Ahmad Fariz Maulana et al [ 58 ] used acarbose as a positive control, but their docking results did not accurately reflect the in vitro experimental results. In this study, α-mangostin was demonstrated to be a potent α -glucosidase inhibitor, with an IC 50 value of 1.90 ± 0.10 μg/mL (equivalent to 4.63 ± 0.24 μM), whereas the IC 50 value of acarbose was 134.56 ± 3.02 μg/mL (equivalent to 204.93 ± 4.60 μM).…”
Section: Resultsmentioning
confidence: 99%
“…Various drugs have been used to treat T2DM, including insulin, acarbose, rosiglitazone, metformin, and sulfonylureas. These drugs can cause various side effects, including gastrointestinal symptoms [16]. Only a few of these drugs are approved for consumption by children.…”
Section: Introductionmentioning
confidence: 99%